The Amazon as Inspiration: How to Integrate Sustainability and Cultural Themes into Board Games - Nascimento, Beatriz Rodrigues; Alencar, Larissa Albuquerque de (DAT Journal, 2026)
This article explores the use of board games as a tool to promote environmental education and cultural appreciation of the Amazon. The research, based on a literature review, analyzes existing games and identifies elements that make these games effective in integrating sustainability and culture. The study also investigates the opportunities and challenges in developing games with this theme, considering the social and economic impact on local communities. The immersion provided by games is highlighted as essential for connecting the public to socio-environmental issues. It is hoped that the study will contribute to the creation of more effective games, promoting environmental awareness, learning about the Amazon and sustainable development.